Die Wahrnehmung von und Beziehung zu Geistlichen in evangelischen und römisch- katholischen Gemeinden - Sarah F. Tichy (Zeitschrift für Junge Religionswissenschaft)
The present study focuses on the perception of clerics in Lutheran, Reformed and Roman-Catholic communities. In addition, the relationship between believers and clergymen, the believers’ own religiosity and their relationship to and perception of God are included. The empirical study is based on the attachment theory of John Bowlby (1969; 1973). 63 subjects from Germany and Austria, who either are involved in the Lutheran, in the Reformed or in the Roman-Catholic church and who indicated that they had closer contact to clerics, were retrospectively questioned through a computer-based survey about their youth. It can be shown that the clergyman was estimated as generally positive, emotionally empathetic and sensitive. In some cases there is evidence of a deeper relationship between believer and cleric where believers reported to approach the cleric with their sorrows and problems. Lutheran and Reformed individuals rated the sensitivity of the clergyman higher than the Roman-Catholic subjects. There were no significant denominational differences concerning the relationship to and perception of God and their own religiosity. Limitations of the study, points of critics and further subsequent issues are discussed.